Post-Soviet Masculinity: Unnoticed or Excluded Agenda? (II) - Kraniauskas, Liutauras (Sociologija. Mintis ir veiksmas, 2010)
The paper contributes a concept of post-Soviet masculinity to the masculinity discourse of the post-communist societies. Short overview of the main studies on men and masculinities in the territory of ex-Soviet Union and Lithuania misses idea of historicity, which might be compensated by the concept of post-Soviet masculinity. Three conceptual papers of A.Juska (2003), S.Oushakin (2002) and A.Tereskinas (2008) suggests few insights on the content of the post-Soviet masculinity. Critical analysis of three conceptual suggestions is finalized in more concrete understanding of the post-Soviet masculinity as a concept defined by historicity.